Determination and Correlation of Electrolytes and Trace Elements from Vitreous Humour and Synovial Fluid by Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) for Estimation of Post-Mortem Interval (PMI): Experimental Study in an Animal Model - Panjai Woharndee1 , Jutapit Prungkramphun2, Sarawut Kumphune3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The estimation of post-mortem interval (PMI) procedures seem to subjectivity in assessment and lesssensitivity and specificity. Biochemical determination of trace elements from closed-system samples,such as vitreous humour (VH) and synovial fluid (SF) is an alternative laboratory investigation for PMIestimation. The inductively coupled plasma-mass spectrometry (ICP-MS) provides more rapid, precise andsensitive analysis of elements samples. However, determination of electrolytes and trace elements in VHand SF by ICP-MS, and application for PMI has not been intensively investigated. In this study, VH andSF from twenty adult domesticated pig carcasses were collected at 1, 3, 6, 12, 24, 36, and 48-hour afterdeath. Samples were analysed for total protein concentration, Ca, Cu, Fe, K and, Na using ICP-MS. Theresults showed that the protein concentration in VH was significantly increased in time dependent manner,but not for SF. The level of K and Fe in both VH and SF increased in time dependent manner, with a goodcorrelation between both sample sources. The calcium concentration of both VH and SF increased in timedependent manner, but there was no correlation between both sample sources. Sodium was significantlyreduced at 36-48 h, with a correlation between both sample sources. However, the copper level in VH wasincreased at 36-48 h but reduced in SF. In conclusion, this study showed for the first time that multiple traceelements and electrolytes could be detected, using the ICP-MS, in both of VH and SF simultaneously andadditionally its correlation.